Acute and Chronic Administrations of Rheum palmatum Reduced the Bioavailability of Phenytoin in Rats: A New Herb-Drug Interaction. (8th July 2012) - Chi, Ying-Chang; Juang, Shin-Hun; Chui, Wai Keung; Hou, Yu-Chi; Chao, Pei-Dawn Lee
Abstract : The rhizome of Rheum palmatum (RP) is a commonly used herb in clinical Chinese medicine. Phenytoin (PHT) is an antiepileptic with narrow therapeutic window. This study investigated the acute and chronic effects of RP on the pharmacokinetics of PHT in rat. Rats were orally administered with PHT (200 mg/kg) with and without RP decoction (single dose and seven doses of 2 g/kg) in a crossover design. The serum concentrations of PHT, PHT glucuronide (PHT-G), 4-hydroxyphenytoin (HPPH), and HPPH glucuronide (HPPH-G) were determined by HPLC method. Cell line models were used to identify the underlying mechanisms. The results showed that coadministration of single dose or multiple doses of RP significantly decreased the C max and AUC0-t as well as the K 10 of PHT, PHT-G, HPPH, and HPPH-G. Cell line studies revealed that RP significantly induced the P-gp-mediated efflux of PHT and inhibited the MRP-2-medicated transport of PHT and HPPH. In conclusion, acute and chronic coadministrations of RP markedly decreased the oral bioavailability of PHT via activation of P-gp, although the MRP-2-mediated excretion of PHT was inhibited. It is recommended that caution should be exercised during concurrent use of RP and PHT. Erratum to "Acute and Chronic Administrations of Rheum palmatum Reduced the Bioavailability of Phenytoin in Rats: A New Herb-Drug Interaction" dx.doi.org/10.1155/2013/870309